ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP MOTIVASI KERJA STAF YAYASAN STIMI YAPMI MAKASSAR - Mardiana Ibrahim (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2011)
Compensation is very important because of this will tepenuhi basic necessities that will push to do a good job, if compensation is given full and correct on the foundation staff will gain job satisfaction and motivated to achieve goals. If compensation is inadequate or inaccurate then the automatic effect on motivation and achievement decline. one of them by raising or giving appropriate compensation to be motivated to perform better can be further enhanced